Barbarian's mate - Dixon, Ruby, 1976- (Dixon, Ruby, 1976- Ice planet barbarians series, 2023)
"The next novel in the international publishing phenomenon the Ice Planet Barbarians series, now in a special print edition with a bonus novella! Josie has always dreamed of finding The One, but the hunter chosen for her is nothing like what she expected (or wanted)--but he might be exactly what she needs. "Resonance" is supposed to be a dream--that's when your soulmate is chosen for you. And every woman on the ice planet has hooked up with a big, hunky soulmate of their own--except me. So do I want a mate? Heck yeah. More than anything, all I've ever wanted is to be loved by someone. But the soulmate chosen for me? My least favorite person on the darn ice planet. Haeden's the most cranky, disapproving, unpleasant, overbearing male alien . . . so why is it that my body sings when he gets close? Why is he working so hard to prove to me that he's not as awful as I think he is? I hate him . . . don't I?"--